Complete replacement of fish oil and fish meal in the diet of juvenile California yellowtail Seriola dorsalis. (7th October 2020) - Stuart, Kevin R.; Barrows, Frederic T.; Silbernagel, Constance; Alfrey, Kelly; Rotstein, David; Drawbridge, Mark A.
Abstract: California yellowtail (CYT) Seriola dorsalis is a top candidate for aquaculture in southern California. CYT is fed commercial diets whose nutrient profile and ingredient composition rely heavily on fish meal and fish oil. We evaluated the complete replacement of fish oil and fish meal with a Schizochytrium ‐derived algal oil as an essential fatty acid source and poultry by‐product meal and spirulina as primary protein sources, in the diet of juvenile CYT (average initial weight—19.95 ± 0.09 g). The treatment diets for this study included the following: FMF‐FO—fish meal free, fish oil; FMF‐AO—fish meal free, algal oil; FMF‐SO—fish meal free, soybean oil; FMC‐FO—fish meal control, fish oil. Each treatment diet was formulated to contain 45% protein and 15% lipid, and the trial lasted 64 days. At the conclusion of the trial, fish from FMC‐FO group had performed significantly better in three key performance metrics: final body weight of 185.96 ± 8.98 g, per cent weight gain of 832.7 ± 47.2% and lowest FCR of 1.16 ± 0.04. Replacing fish meal with poultry by‐product meal and spirulina resulted in 20% less weight gain. Replacing fish oil with algal oil, in a fish meal free diet, resulted in equal weight gain, and the fish had higher tissue essential fatty acid content. Based on the results from this trial, we have shown that in CYT juvenile diets, fish oil can be replaced with algal oil with no effect on growth or survival and fish meal can be replaced with no effect on survival and a 20% decrease in weight gain.